Analysis of the Application of Edward Thordinke's Behavioristic Theory in increasing interest in learning science for Grade 6 students - Maharani Ayu Ningrum; Ni Ketut Suarni; I Gede Margunayasa (Psikostudia : Jurnal Psikologi, 2025)
This research was conducted in response to the challenges and low interest in learning from grade 6 elementary school students in science learning. The purpose of this study is to overcome the low interest in learning grade 6 students in science learning by applying behavioristic theory by Edward Thorndike. This study also aims to overcome the low interest in learning grade 6 students in learning Mathematics by using behavioristic theory in the context of science learning. Grade 6 students were divided into two groups, namely the experimental group and the control group, using the Purposive Random Sampling Technique. Science learning ability data were collected through the test method, and data analysis was performed using the Polled Variance T test due to the homogeneity of the data variance. The results showed a significant difference in science learning ability between the group that applied the Behavioristic of Edward ThorndikeTheory and the control group. The findings of this study have important implications in designing effective learning strategies in the future, focusing on curriculum development and learning approaches that can increase students' understanding and interest in learning. This research also makes a significant contribution in efforts to improve the quality of science learning in elementary schools, both conceptually and applicatively. Penelitian ini dilakukan sebagai respons terhadap tantangan dan minat belajar yang rendah dari siswa kelas 6 Sekolah Dasar dalam pembelajaran IPA. Tujuan penelitian ini adalah mengatasi rendahnya minat belajar siswa kelas 6 dalam pembelajaran IPA dengan menerapkan teori behavioristik oleh Edward Thorndike. Penelitian ini juga bertujuan untuk mengatasi rendahnya minat belajar siswa kelas 6 dalam pembelajaran IPA dengan menggunakan teori behavioristik dalam konteks pembelajaran IPA. Siswa kelas 6 dibagi menjadi dua kelompok, yaitu kelompok eksperimen dan kelompok kontrol, dengan menggunakan Teknik Purposive Random Sampling. Data kemampuan pembelajaran IPA dikumpulkan melalui metode tes, dan analisis data dilakukan menggunakan uji T Polled Varians karena homogenitas varians data. Hasil penelitian menunjukkan adanya perbedaan signifikan dalam kemampuan pembelajaran IPA antara kelompok yang menerapkan Teori Behavioristik oleh Edward Thorndikedan kelompok kontrol. Temuan penelitian ini memiliki implikasi penting dalam merancang strategi pembelajaran yang efektif di masa depan, dengan fokus pada pengembangan kurikulum dan pendekatan pembelajaran yang dapat meningkatkan pemahaman dan minat belajar siswa. Penelitian ini juga memberikan kontribusi yang signifikan dalam upaya meningkatkan mutu pembelajaran IPA di Sekolah Dasar, baik secara konseptual maupun aplikatif.